Republic of Kosovo : First Review Under the Stand-by Arrangement and Request for Modification and Waivers of Applicability of Performance Criteria-Press Release; Staff Report; and Statement by the Executive Director for the Republic of Kosovo. (IMF Staff Country Reports; Country Report ;, 2016)
This paper discusses Kosovo's First Review Under the Stand-By Arrangement and Requests for Modification and Waivers of Applicability of Performance Criteria (PC). The program is on track. All end-August 2015 PCs and indicative targets were met by comfortable margins. All structural benchmarks for the first review have been met. More broadly, there is strong ownership of structural reforms in the financial sector and in public procurement. The authorities reaffirmed the targets for the fiscal deficit and bank balances for next year and identified measures to achieve these. The IMF staff support the authorities' request for completion of the first review.